2023
DOI: 10.3390/ph16101495
|View full text |Cite
|
Sign up to set email alerts
|

Profiling Analysis of Tryptophan Metabolites in the Urine of Patients with Parkinson’s Disease Using LC–MS/MS

So Hyeon Chung,
Dallah Yoo,
Tae-Beom Ahn
et al.

Abstract: Although Parkinson’s disease (PD) is a representative neurodegenerative disorder and shows characteristic motor impediments, the pathophysiological mechanisms and treatment targets for PD have not yet been clearly identified. Since several tryptophan metabolites produced by gut microbiota could pass the blood–brain barrier and, furthermore, might influence the central nervous system, tryptophan metabolites within the indole, kynurenine, and serotonin metabolic pathways might be the most potent targets for PD d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…This suggests that it is challenging to find appropriate targets to develop the drug, since Parkinson's disease is a multifactorial disease (Yadav and Kumar 2022). Furthermore, to investigate non-motor symptoms of Parkinson's disease, it was reported that an LC-MS/MS method was developed to profile tryptophan metabolites, including microbial produced neurotransmitters in human urine samples (Chung et al 2023).…”
Section: Potential Biomarkers Related To Neurological Diseasesmentioning
confidence: 99%
“…This suggests that it is challenging to find appropriate targets to develop the drug, since Parkinson's disease is a multifactorial disease (Yadav and Kumar 2022). Furthermore, to investigate non-motor symptoms of Parkinson's disease, it was reported that an LC-MS/MS method was developed to profile tryptophan metabolites, including microbial produced neurotransmitters in human urine samples (Chung et al 2023).…”
Section: Potential Biomarkers Related To Neurological Diseasesmentioning
confidence: 99%
“…The urine samples were taken in the interictal period 10-30 days after the last migraine attack, which corresponded to the last administration of headache abortive drugs. L-tryptophan and its following metabolites: 5-HIAA, KYN, KYNA, and QA were determined in urine with liquid chromatography-tandem mass spectrometry (LC-MS/MS-Ganzimmun Diagnostics AG, Mainz, Germany; D-ML-13147-01-01), as described elsewhere [61] with some modifications [62]. The concentration of TRP and its metabolites were expressed in mg/g creatinine (mg/gCr).…”
Section: Determination Of Trp Metabolitesmentioning
confidence: 99%
“…The urine samples were taken in the interictal period 10-30 days after the last migraine attack, which corresponded to the last administration of headache abortive drugs. L-tryptophan and its following metabolites: 5-HIAA, KYN, KYNA, and QA were determined in urine with liquid chromatography-tandem mass spectrometry (LC-MS/MS-Ganzimmun Diagnostics AG, Mainz, Germany; D-ML-13147-01-01) as described elsewhere [56] with some modifications [57]. The concentration of TRP and its metabolites were expressed in mg/g creatinine (mg/gCr).…”
Section: Determination Of Trp Metabolitesmentioning
confidence: 99%